Walk 13 MEETINGS WITH GAIDAI - Lidin, Konstantin; Grigoryeva, Elena; Chumakov, Sergey; Makogon, Lyubov (project baikal, 2014)
Walk 13 MEETINGS WITH GAIDAILeonid Gaidai's HouseDevelopment of Gaidai BoulevardExtension of East-Siberian Railway School-Lyceum №42 on Profsoyuznaya StreetAdministration and Amenity BuildingPonton BridgeHabitable Bridge in Irkutsk. Term Theses